Future risk of cardiovascular disease risk factors and events in women after a hypertensive disorder of pregnancy. Issue 16 (7th June 2019) - Benschop, Laura; Duvekot, Johannes J; Roeters van Lennep, Jeanine E
Abstract : Hypertensive disorders of pregnancy (HDP), such as gestational hypertension and pre-eclampsia, affect up to 10% of all pregnancies. These women have on average a twofold higher risk to develop cardiovascular disease (CVD) later in life as compared with women with normotensive pregnancies. This increased risk might result from an underlying predisposition to CVD, HDP itself or a combination of both. After pregnancy women with HDP show an increased risk of classical cardiovascular risk factors including chronic hypertension, renal dysfunction, dyslipidemia, diabetes and subclinical atherosclerosis. The prevalence and onset of cardiovascular risk factors depends on the severity of the HDP and the coexistence of other pregnancy complications. At present, guidelines addressing postpartum cardiovascular risk assessment for women with HDP show a wide variation in their recommendations. This makes cardiovascular follow-up of women with a previous HDP confusing and non-coherent. Some guidelines advise to initiate cardiovascular follow-up (blood pressure, weight and lifestyle assessment) 6–8 weeks after pregnancy, whereas others recommend to start 6–12 months after pregnancy. Concurrent blood pressure monitoring, lipid and glucose assessment is recommended to be repeated annually to every 5 years until the age of 50 years when women will qualify for cardiovascular risk assessment according to all international cardiovascular prevention guidelines.